Bunny's pellet: natural mulberry pellet / Nor Dini Rusli ... [et al.] - Rusli, Nor Dini; Mat, Khairiyah; Che Harun, Hasnita; Mahmud, Mohd; Syed Abd. Kadir, Syed Muhammad Al-Amsyar (2021)
Rabbit farming is a thriving industry in Malaysia. Normally in rabbit production farm, farmers use commercial pellet as the main diet of the rabbits and feed is the main expense as it accounts for between 70 to 80% of animal production. In fact, the prices of commercial pellet in recent years have increased, making the rabbit farming more expensive. Mulberry (Morus spp) is one of the legumes that is highly palatable and digestible to herbivorous and monogastric animals. Crude protein in mulberry leaves can go up to 18.9 to 21.9%. Mulberry leaves have a good potential to replace the concentrate in the rabbit feed and can be used as the main feed for rabbits. However, the rabbits tend to pick all the high sugar and low fibre bits only from the fresh hay or green leave. Hence, in the current study, mulberry leave with other ingredients were processed into uniform pellets for a balanced nutrient source; called Bunny's pellets. This Bunny's pellet can be a new replacement of commercial pellet as it contains similar nutritional values as a commercial pellet. The benefits of Bunny's pellet include high crude protein, nutritional values similar to the imported commercial pellet, low cost compared to commercial pellet as well as no artificial colour and preservatives. The product was tested in a 60-day rabbit feeding trial using 15 New Zealand White cross California rabbits. The findings demonstrated that the Bunny's pellets are high in terms of digestibility and palatability, good feed intake, thus promoting a satisfactory weight gain in rabbits. The average daily gain and feed conversion ratio of the results were not significantly different between control (commercial pellet) and mulberry pellet. A few industries and university that we worked with closely on the development of this Bunny's pellets are Persatuan Penternak Arnab Pedaging (APEK), Taman Arnab IQ, Bumi Barakah Agro Enterprise and Universiti Malaysia Terengganu. This product has been published in two undergraduate theses, a book chapter, and a journal article (in review). This product was previously awarded a Silver medal in UMK Carnival of Research & Innovation 2019.